Family Reaction as a Developmental Turning Point Among Formerly Incarcerated LGBTQ + Adults - Morgan, Skyler (Journal of developmental and life-course criminology, 2024)
Family reaction to LGBTQ + identity is a complex developmental experience that can lead to various outcomes for LGBTQ + people. Prior scholarship has identified family rejection as a risk factor for poor mental, physical, and social outcomes and family acceptance as a protective factor. However, little scholarship has considered the developmental role of family reaction to LGBTQ + identity on offending and desistance trajectories or explored the experiences with family reaction among LGBTQ + people who have had contact with the criminal legal system. This paper addresses this gap in the literature by centering the role of family reaction to LGBTQ + identity among formerly incarcerated LGBTQ + people. More specifically, this paper draws on original data collected from life history interviews with 25 formerly incarcerated LGBTQ + people. This qualitative work considers (1) their experiences with family reactions, (2) family reaction as a developmental turning point, and (3) navigating the criminal legal system with complex family dynamics. Findings indicated that the majority of the sample encountered some form of rejection (subtle and/or explicit) from their families, which was shaped by other LGBTQ + family members and generational, structural, religious, and political factors. Family reaction functioned as a developmental turning point that impacted offending (rejection) and desistance (acceptance). This work holds important policy implications, including the need for support groups for LGBTQ + people experiencing family rejection inside and outside of criminal legal contexts.